2016
DOI: 10.1007/s00232-016-9886-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fatty Acid Methyl Esters (FAMEs) in the Biochemistry and the Na+/K+-ATPase Activity of Culex quinquefasciatus Larvae

Abstract: Culex quinquefasciatus is the main vector of lymphatic filariasis and combating this insect is of great importance to public health. There are reports of insects that are resistant to the products currently used to control this vector, and therefore, the search for new products has increased. In the present study, we have evaluated the effects of fatty acid methyl esters (FAMEs) that showed larvicidal activity against C. quinquefasciatus, on glucose, total protein, and triacylglycerol contents and Na(+)/K(+)-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Recent studies have illustrated the function of Na ϩ /K ϩ -ATPase in osmoregulation of crustaceans, neurological cancers, and therapeutic targets for diseases (18 -20). Na ϩ /K ϩ -ATPase is also reported as an efficient target of insecticides (21,22). Whereas extensive studies have been carried out to elucidate the function of Na ϩ / K ϩ -ATPase in controlling the ion transport through cell membranes, the regulatory cascade of Na ϩ /K ϩ -ATPase activity in JH-dependent initiation of patency has been lacking.…”
mentioning
confidence: 99%
“…Recent studies have illustrated the function of Na ϩ /K ϩ -ATPase in osmoregulation of crustaceans, neurological cancers, and therapeutic targets for diseases (18 -20). Na ϩ /K ϩ -ATPase is also reported as an efficient target of insecticides (21,22). Whereas extensive studies have been carried out to elucidate the function of Na ϩ / K ϩ -ATPase in controlling the ion transport through cell membranes, the regulatory cascade of Na ϩ /K ϩ -ATPase activity in JH-dependent initiation of patency has been lacking.…”
mentioning
confidence: 99%
“…The insecticidal activity of this extract was contributed to by octadecanoic acid and stearic acid, leading to a low LC 50 of this extract (16.92 mg/ml), as inferred in a previous study. A study described in 72 proved that a formulation of fatty acid methyl ester (FAME) that consists of methyl stearate showed larvicidal activity against C. quinquefasciatus. The previous study showed that the insecticidal activity of this compound occurred through ingestion, which is in consistent with and validated the result of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acids found in the leaves are responsible for controlling water loss to the environment during gas exchanges, and protect the plant against the nutrient loss due to the high incidence of ultraviolet rays and intense rainfall (Kozlowski & Pallardy, 1996); in the flowers, as well as in the leaves, the fatty acids are part of the surface impermeabilization, avoiding water loss, and part of the pollination process as they are in the chemical composition of flower nectar (Levin, McCue, & Davidowitz, 2017) whereas, in the fruits and seeds, these acids act as a barrier to moist diffusion, as a form of protection, because it is a reserve organ to the embryo (Esau, 1986;Kunst & Samuels, 2009). In general, fatty acids act on the cellular structure of vegetables, growth, nutrition, senescence, and protection against phytopathogens and the environment (Meï et al, 2015;Li, Xu, Li-Beisson, & Philippar, 2016;Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The linoleic acid ethyl ester as well as the linolenic acid methyl ester are present in the dark green leaves because they are part of the apolar lipid fraction of plants (Simopoulos, 2002). There are no reports on the activity of these molecules against A. aegypti, but fatty acid methyl ester had LC 99.9 of 0.17 mg/mL in Culex quinquefasciatus larvae (Silva et al, 2016), indicating insecticide effect against larvae of this insect.…”
Section: Discussionmentioning
confidence: 99%